A general one-pot strategy for the synthesis of Au@multi-oxide yolk@shell nanospheres with enhanced catalytic performance. Issue 38 (20th August 2018) - Li, Jian; Song, Shuyan; Long, Yan; Yao, Shuang; Ge, Xin; Wu, Lanlan; Zhang, Yibo; Wang, Xiao; Yang, Xiangguang; Zhang, Hongjie
Abstract : By integrating redox self-assembly and redox etching processes, we report a general one-pot strategy for the synthesis of Au@multi-M x O y (M = Co, Ce, Fe, and Sn) yolk@shell nanospheres. Abstract : By integrating redox self-assembly and redox etching processes, we report a general one-pot strategy for the synthesis of Au@multi-M x O y (M = Co, Ce, Fe, and Sn) yolk@shell nanospheres. Without any additional protecting molecule or reductant, the whole reaction is a clean redox process that happens among the inorganic metal salts in an alkaline aqueous solution. By using this method, Au@Co3 O4 /CeO2 (Au@Co–Ce), Au@Co3 O4 /Fe2 O3 (Au@Co–Fe), and Au@CeO2 /SnO2 (Au@Ce–Sn) yolk@shell nanospheres with binary oxides as shells, Au@Co3 O4 /CeO2 /Fe2 O3 (Au@Co–Ce–Fe) yolk@shell nanospheres with ternary oxides as shells and Au@Co3 O4 /CeO2 /Fe2 O3 /SnO2 (Au@Co–Ce–Fe–Sn) yolk@shell nanospheres with quaternary oxides as shells can be obtained. Subsequently, the catalytic CO oxidation was selected as the catalytic model, and the Au@Co–Ce system was chosen as the catalyst. It was found that the catalytic activity of Au@Co–Ce yolk@shell nanospheres can be optimized by altering the relative proportion of Co and Ce oxides.